Variáveis explicativas da cotação de seguros por canais digitais - Manna, Paulo Daniel (2016)
As information technology has changed people's and business communication, e-commerce and digital marketing have become critical to most businesses. As the new channel and new technologies are constantly evolving, new possibilities and relationships for both business and consumers arise, although one aspect remains of great importance for professionals: to determine consumers’ factors and motivations to use digital channels. This study presents a quantitative study (logistic regression) on the influence of demographic variables, such as sex, age and income, on the propensity to purchase car insurance through electronic channels. The results did not allow to identify relevant differences in relation to the gender and age of consumers, but income was identified as an influence factor, so consumers with higher income are more likely to choose digital channels for acquiring car insurance, in line with previous studies. The dissertation presents implications for the area of Marketing and for the practice of the insurance market, along with suggestions of future studies.